Simulation and optimization for a plastic component. Issue 1 (June 2020) - Pashte, Samhita; Wagle, Kiran; Agrawal, Shailesh; Sudhakar, D S S; Patil, Bhushan; Singraur, Deepika S
Abstract: This paper presents the simulation of injection moulding process of the subject component and noting the deflection results using finite element software. Subsequently some changes were made to the tool and part design of the subject component and the modifications which gave the minimum deflection were incorporated and used for further optimization of warpage using design of experiments.